Self-Assessment Metacognitive Strategies in A Spontaneous ESL Speech Production Context - Tharmalingam, Komalah; Asmawi, Adelina; Lim, Jia Wei (UUM PRESS, 2024)
Purpose – Self-assessment is regarded as a complex metacognitive process by scholars. Nevertheless, in the context of English as a Second Language (ESL) speaking, self-assessment practices often rely on assessment criteria and teacher commentaries. However, speaking involves spontaneous expression with limited access to external standards. Therefore, this case study aims to explore the metacognitive strategies that proficient ESL students use during self assessment in spontaneous speech production contexts. Methodology – Three participants, purposefully selected, participated in two spontaneous group discussions recorded on video. Instances of participants’ dysfluency served as prompts in stimulated recall interviews, complemented by video recordings to validate participants’ responses. The thematic analysis of interview data utilised a conceptual framework integrating O’Malley and Chamot’s (1990) metacognitive strategies and Kormos’ (2006) speech production model Findings – The analysis revealed that participants employed three key metacognitive strategies – organisational planning, selective attention, and self-monitoring to self-assess their spontaneous speech. Feedback sources, such as their proficiency in the second language (L2) and contextual factors, influenced the application and effectiveness of these strategies during self-assessment (SA). Significance – This study offers insights into how proficient ESL students self-assess their spontaneous speech production, leveraging their available resources. In addition, this study identifies speech challenges the participants encountered and how they applied metacognitive strategies to address them